An overview of novel proteins in reformulated food - Franco D. (2023)
© 2024 Elsevier Inc. All rights reserved.Searching for novel proteins but paraphrasing famous Marx brothers, “…and two hard-boiled eggs!.” To address climate change and ethical aspects of animal production seriously, the food industry should seek alternative protein sources as well as improve the yield and quality of traditional protein food. Novel sources based on vegetable origin (pulses or microalgae), fungi, bacteria, and/or insects will be critical in the coming years. A wide range of proteins could be used to prepare meat alternatives for vegan foods. Even, hydrolysates with health-promoting effects should be included in our diet.